Characterization of an aerosol microconcentrator for analysis using microscale optical spectroscopies. (February 2017) - Zheng, Lina; Kulkarni, Pramod; Zavvos, Konstantinos; Liang, Huayan; Birch, M. Eileen; Dionysiou, Dionysios D.
Abstract: Efficient microconcentration of aerosols to a substrate is essential for effectively coupling the collected particles to microscale optical spectroscopies such as laser-induced or spark microplasma, or micro-Raman or infrared spectroscopies. In this study, we present detailed characterization of a corona-based aerosol microconcentration technique developed previously (Diwakar & Kulkarni, 2012). The method involves two coaxial electrodes separated by a few millimeters, one held at a high electrical potential and the other grounded. The particles are collected on the collection (i.e., ground) electrode from a coaxial aerosol flow in a one-step charge-and-collect scheme using corona discharge and electrical precipitation between the two electrodes. Performance of the corona microconcentration method was determined experimentally by measuring collection efficiency, wall losses, and particle deposition density. An intrinsic spectroscopic sensitivity was experimentally determined for the aerosol microconcentrator. Using this sensitivity, we show that corona-based microconcentration is much superior to alternative methods, including filtration, focused impaction using aerodynamic lens, and spot collection using condensational growth. The method offers unique advantages for compact, hand-held aerosol analytical instrumentation. Highlights: Characterization of corona-assisted microconcentration method for submicrometer aerosol reported. The method achieves effective coupling with microscale optical spectroscopies. Highly efficient compared to aerodynamic lens or spot collection using aerosol magnification. Method allows orders of magnitude reduction in detection limits and/or time resolution of aerosol analysis.